Intranasal Delivery of Apelin-13 Is Neuroprotective and Promotes Angiogenesis After Ischemic Stroke in Mice - Chen, Dongdong (ASN Neuro, 2015)
Apelin is a peptide originally isolated from bovine stomach tissue extracts and identified as an endogenous ligand of the APJ receptor; recent work showed that apelin ameliorates the ischemic injury in the heart and the brain. Being an analogue to the angiotensin II receptor, the apelin/APJ signaling may mediate angiogenesis process. We explored the noninvasive intranasal brain delivery method and investigated therapeutic effects of apelin-13 in a focal ischemic stroke model of mice. Intranasal administration of apelin-13 (4 mg/kg) was given 30 min after the onset of stroke and repeated once daily. Three days after stroke, mice received apelin-13 had significantly reduced infarct volume and less neuronal death in the penumbra. Western blot analyses showed upregulated levels of apelin, apelin receptor APLNR, and Bcl-2 and decreased caspase-3 activation in the apelin-13-treated brain. The proinflammatory cytokines tumor necrosis factor-alpha, interleukin-1β, and chemokine monocyte chemoattractant protein-1 mRNA increased in the ischemic brain, which were significantly attenuated by apelin-13. Apelin-13 remarkably reduced microglia recruitment and activation in the penumbra according to morphological features of Iba-1-positive cells 3 days after ischemia. Apelin-13 significantly increased the expression of angiogenic factor vascular endothelial growth factor and matrix metalloproteinase-9 14 days after stroke. Angiogenesis illustrated by collagen IV + /5-bromo-2′-deoxyuridin + colabeled cells was significantly increased by the apelin-13 treatment 21 days after stroke. Finally, apelin-13 promoted the local cerebral blood flow restoration and long-term functional recovery. This study demonstrates a noninvasive intranasal delivery of apelin-13 after stroke, suggesting that the reduced inflammatory activities, decreased cell death, and increased angiogenesis contribute to the therapeutic benefits of apelin-13.